Can antibrowsing defense regulate the spread of woody vegetation in arctic tundra?. Issue 3 (16th December 2013) - Bryant, John P.; Joly, Kyle; Chapin, F. Stuart; DeAngelis, Donald L.; Kielland, Knut
<x xml:space="preserve">Abstract</x> Global climate warming is projected to promote the increase of woody plants, especially shrubs, in arctic tundra. Many factors may affect the extent of this increase, including browsing by mammals. We hypothesize that across the Arctic the effect of browsing will vary because of regional variation in antibrowsing chemical defense. Using birch (Betula) as a case study, we propose that browsing is unlikely to retard birch expansion in the region extending eastward from the Lena River in central Siberia across Beringia and the continental tundra of central and eastern Canada where the more effectively defended resin birches predominate. Browsing is more likely to retard birch expansion in tundra west of the Lena to Fennoscandia, Iceland, Greenland and South Baffin Island where the less effectively defended non‐resin birches predominate. Evidence from the literature supports this hypothesis. We further suggest that the effect of warming on the supply of plant‐available nitrogen will not significantly change either this pan‐Arctic pattern of variation in antibrowsing defense or the resultant effect that browsing has on birch expansion in tundra. However, within central and east Beringia warming‐caused increases in plant‐available nitrogen combined with wildfire could initiate amplifying feedback loops that could accelerate shrubification of tundra by the more effectively defended resin birches. This accelerated shrubification of tundra by resin birch, if extensive, could reduce the food supply of caribou causing population declines. We conclude with a brief discussion of modeling methods that show promise in projecting invasion of tundra by woody plants.